GSTM1 Deletion Compensated in mRNA Expression and 4T1 Viability After Editing Using CRISPR/Cas9 Single and Double gRNA - Emilia Vivi Arsita; Dwi Aris Agung Nugrahaningsih; Ahmad Hamim Sadewa (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Glutathione S-transferase Mu-1 (GSTM1) is known to undergo polymorphism and plays role in drug metabolism including Paclitaxel (PTX), the first-line chemotherapy for breast cancer. However, the effect of GSTM1 polymorphism against chemotherapy in breast cancer is limited and unexplored. This study was conducted to explore the effects of single and double guide (gRNA) on the GSTM1 knocked out (KO) and its effect on the response of PTX in the 4T1 cell line.METHODS: The preparatory stage was done by culturing and electroporating 4T1 cells using Ribonucleoprotein of clustered regularly interspaced short palindromic repeats (CRISPR)/Caspase 9 (Cas9). KO validation was examined by quantitative reverse transcription polymerase chain reaction (qRT-PCR), Sanger sequencing, and ICE analysis. The 4T1 viability was examined by MTT Assay.RESULTS: The number of base pairs of GSTM1 after being engineered by single or double gRNA was 86 bases. The DNA quantity of GSTM1 engineered by gRNA was more than using double gRNAs. The mRNA expression of GSTM1 engineered by single gRNA was lower than using double gRNAs. IC50 values of PTX between wildtype and KO were not significantly different, in the range of 30 µM.CONCLUSION: The base-pair length of GSTM1 exon 4 that is knocked out with single and double gRNA have the same number of base pairs. The quantity of GSTM1 DNA and mRNA expression are contrary between single gRNA and double gRNA, and IC50 PTX values in the 4T1 cell line of the control group with single or double gRNA knocked out do not differ markedly. PTX efficiency as chemotherapy is not disturbed in the GSTM1 deletion genetic profile.KEYWORDS: GSTM1, gRNA, Paclitaxel, CRISPR, breast cancer